1981
DOI: 10.1007/bf00033995
|View full text |Cite
|
Sign up to set email alerts
|

Genetic variation in stomatal characteristics and behaviour, water use and growth of five Vicia faba L. genotypes under contrasting soil moisture regimes

Abstract: Five genotypes of Viciafuba L. with contrasting stomata1 frequencies were grown in a controlled environment in soil moisture regimes of 100x, 78% and 61% of field capacity. Growth, water use and leaf conductance characteristics were measured. Stomata were more frequent on abaxial than adaxial surfaces, the abaxial/adaxial ratio ranging from 1.12 to 1.34. There were significant (P < 0.001) correlations between calculated stomata1 conductance, based on measurements of stomata1 frequency and length, and leaf cond… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
10
0

Year Published

1982
1982
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(12 citation statements)
references
References 15 publications
2
10
0
Order By: Relevance
“…Nerkar et al (1981) found considerable differences in water loss and transpiration in faba bean genotypes having contrasting stomatal features, and suggested that lower transpiration rate would contribute to drought tolerance. Furthermore, excessive water use in the droughtsensitive faba bean cultivar Adriewaalse from Netherlands was associated with its higher transpiration, while L-7, a breeding line of Mediterranean background was modest in water use and hence drought tolerant (Amede et al 1999).…”
Section: Discussionmentioning
confidence: 95%
“…Nerkar et al (1981) found considerable differences in water loss and transpiration in faba bean genotypes having contrasting stomatal features, and suggested that lower transpiration rate would contribute to drought tolerance. Furthermore, excessive water use in the droughtsensitive faba bean cultivar Adriewaalse from Netherlands was associated with its higher transpiration, while L-7, a breeding line of Mediterranean background was modest in water use and hence drought tolerant (Amede et al 1999).…”
Section: Discussionmentioning
confidence: 95%
“…Selection of drought escaping germplasm (White & Singh, 1991) Selection of drought avoidant germplasm (Asfaw & Balir, 2012, Beebe et al, 2013bDevi et al, 2013) Selection of drought tolerant germplasm (Beebe, 2012;Beebe et al, 2008Beebe et al, , 2013aRao et al, 2009Rao et al, , 2013Rao 2014)(Ismail et al, 2000;Hall et al, 2004;Muchero et al, 2009Muchero et al, , 2010(Nerkar et al, 1981;Amede et al, 1999;Link et al, 1999;Khan et al, 2007;Patrick & Stoddard, 2010;Khazaei et al, 2011Khazaei et al, , 2013a(Stoddard et al, 2006) • Early maturing,…”
Section: Common Beanmentioning
confidence: 99%
“…To uncover, understand and exploit genetic variation for stress tolerance, the stress needs to be specified. As an example, level and pattern of applied drought stress varies widely among researchers (e.g., Grzesiak et al, 1997;Nerkar et al, 1981). Under water stress, the plant may find virtually unlimited amount of water yet hard to take up or a limited offer of water as in terminal drought.…”
Section: Faba Beanmentioning
confidence: 99%
“…EISharkawy and Hesketh (1965) showed that in species where stomata were rare or absent on the upper leaf surface, resistance to gas flow was increased, and both photosynthesis and transpiration were reduced. Nerkar et al (1981) found a correlation between stomatal frequency and leaf conductance, but Jones (1977) found that two barley lines which differed in stomatal frequency were similar in leaf conductance, probably because the stomatal pores were larger in the line with lesser numbers.…”
Section: Introductionmentioning
confidence: 95%